Monitor objectivity with important clients: Evidence from auditor opinions around the world - Fung, Simon Yu Kit; Zhou, Gaoguang; Zhu, Xindong (Journal of International Business Studies, 2016)
We examine whether monitors are likely to compromise their monitoring objectivity in the face of economically important clients in international business settings. In the context of external auditing and assurance services, we measure monitor objectivity by whether auditors are more (or less) likely to issue to their important clients modified audit opinions, that is, audit opinions provided to outside investors about the firm that demotes explicit areas of concern. Using a large cross-country sample, we document that auditors are more likely to issue modified opinions to their economically important clients relative to other clients. Furthermore, we find that this association is stronger (1) for Big N auditors, (2) for multinational audit clients, and (3) in countries with stronger legal regimes. These results suggest that monitors prioritize the protection of their reputation over lucrative economic relationships, and such information certification function is more pronounced for international auditors, multinational client firms, and in strong legal regimes.